Hubungan Lingkungan Kerja dan Disiplin Kerja terhadap Performa Karyawan pada PT Dea Warna Abadi - Anggraeni, Natasya; Mei Retno Adiwaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
PT Dea Warna Abadi, a large textile company based in West Jakarta, is currently striving to overcome challenges in achieving sales targets, as well as addressing issues related to the work environment and work discipline that affect employee performance. This study focuses on analyzing how the work environment and work discipline are related to employee performance through a quantitative approach. A total of 50 employees from the marketing division were selected as research subjects using a saturated sampling technique. Data collection was conducted through questionnaires, and the data were then analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The study results revealed that both the work environment and work discipline impact employee performance.